2013
DOI: 10.1002/jssc.201300036
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of 11 isoquinoline alkaloids in Corydalis impatiens (Pall.) Fisch by HPLC

Abstract: Isoquinoline alkaloids are the primary active ingredients of Corydalis, but an analytical method for quality assessment of the active ingredients in Corydalis impatiens (Pall). Fisch has not been reported. A new, simple, and multiple-component quantification method was developed for the simultaneous quantification of 11 isoquinoline alkaloids including capnoidine, chelianthifoline, bicuculline, protopine, isoapocavidine, apocavidine, cavidine, tetrahydroepiberberine, ochotensimine, tetrahydrocoptisine, and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Sample stability of 48 h was examined by repeatedly injecting the same sample solution every 24 h. A recovery test was then used to assess the accuracy of the method. Three concentration levels of reference substances (approximately equivalent to 80, 100, and 120% levels of target compounds) were added with two parallels at each level and analyzed in the same way . The isolation and purification procedure is summarized in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Sample stability of 48 h was examined by repeatedly injecting the same sample solution every 24 h. A recovery test was then used to assess the accuracy of the method. Three concentration levels of reference substances (approximately equivalent to 80, 100, and 120% levels of target compounds) were added with two parallels at each level and analyzed in the same way . The isolation and purification procedure is summarized in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…There are several publications on determining alkaloids in Yuanhu or coumarins in Baizhi , but no method regarding simultaneous quantification of eight alkaloids and three coumarins from the herb pair in situ using an LC–MS/MS method is available. Wan et al reported the simultaneous determination of three coumarins in 12 min and Gao et al published their method for assaying four alkaloids simultaneously in 22 min.…”
Section: Resultsmentioning
confidence: 99%
“…Several analytical methods were reported for the determination of some components in Yuahu‐Baizhi herb‐pair individually or in other combinations in pharmaceutical formulations and in biological matrices. However, there was no method available for the simultaneous determination of major active components in rat intestinal perfusion fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Quality assessment of isoquinoline alkaloids in herbs of Corydalis impatiens (Pall.) Fisch was implemented with mobile phase containing SDS [43]. In addition, TFA can also be considered as an effective ion‐pairing reagent [44].…”
Section: Chromatographic Separation Methodsmentioning
confidence: 99%